Gloss to the judgment of the Provincial Administrative Court in Cracow of 11 January 2021, II SA/Kr 652/20 (approval) - Trzcińska, Diana (Studia Iuridica Toruniensia, 2023)
The author examines the judgment of Voivod Administrative Court in Krakow, accepting the court’s position about declaring the invalidity of the resolution of Municipality Council concerning local law of planning and development, because of the lack of establishing the obligatory urban parameters and indicators for building in the planning unit indicated as forest on which the authority allowed buildings connected with forestry.